The Role of Self-Efficacy As A Moderation of The Influence of Individual Characteristics and Work Professionalism on Employee Performance - Dwi Kusuma Wijaya; Mulyono; Soedjono (Optima Science, 2025)
Performance is a very important and interesting part because it has proven to be very important, an institution wants employees to work hard according to their abilities to achieve good work results, without good performance from all employees, success in achieving goals will be difficult to achieve. Performance basically includes mental attitudes and behaviors that always have the view that the work carried out at this time must be of better quality than the implementation of past work, for the future to be of better quality than at present. The purpose of this study was to determine the role of self-efficacy as a moderator of the influence of individual characteristics and work professionalism on employee performance (Study on Malang Strudle Souvenirs from Malang City). Data collection using questionnaires or by providing a list of questions to respondents. While the analysis method uses the Structural Equation Model - Partial Least Square (SEM-PLS) with the help of the SmartPLS tool. From the results of the study, individual characteristics have a significant effect on employee performance. Work professionalism has a significant effect on employee performance. Self-efficacy has a significant effect on employee performance. Individual characteristics do not have a significant effect on employee performance moderated by self-efficacy. Work professionalism does not have a significant effect on employee performance moderated by self-efficacy.